2007
DOI: 10.1002/jcb.21583
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin protects mesangial cells from hyperglycemia‐induced oxidative signaling

Abstract: Astaxanthin (ASX) is a carotenoid that has potent protective effects on diabetic nephropathy in mice model of type 2 diabetes. In this study, we investigated the protective mechanism of ASX on the progression of diabetic nephropathy using an in vitro model of hyperglycemia, focusing on mesangial cells. Normal human mesangial cells (NHMCs) were cultured in the medium containing normal (5 mM) or high (25 mM) concentrations of D-glucose. Reactive oxygen species (ROS) production, the activation of nuclear transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 48 publications
6
67
0
1
Order By: Relevance
“…3). The accumulation of Ax in mitochondria has been reported in other cell and tissue types, including leukocytes [33], mesangial cells [25], liver, and muscles [45]. The result of our present study suggests the direct action of Ax on mitochondria in bovine preimplantation embryos.…”
Section: Discussionsupporting
confidence: 81%
“…3). The accumulation of Ax in mitochondria has been reported in other cell and tissue types, including leukocytes [33], mesangial cells [25], liver, and muscles [45]. The result of our present study suggests the direct action of Ax on mitochondria in bovine preimplantation embryos.…”
Section: Discussionsupporting
confidence: 81%
“…Increased production of ROS in mitochondria consequent to excessive glucose metabolism has been proposed to mediate the detrimental effects of high glucose by inhibiting glyceraldehyde-3 phosphate dehydrogenase and increasing flux through side pathways in glycolysis (23,31,38). Nevertheless, we and others have shown that NADPH oxidase is actually the predominant source of ROS in mesangial cells exposed to high glucose (16,24,63).…”
Section: Discussionmentioning
confidence: 88%
“…Another report showed that UCP2 was negatively associated with H 2 O 2 production in kidney mitochondria of diabetic rats (79). Manabe et al (208) reported that high glucose increased ROS fluorescence in human mesangial cells associated with potentially harmful cytokine expression, an effect that was blocked by astaxanthin, a carotenoid that accumulated in mitochondria. High glucose also reportedly increased H 2 O 2 production by dichlorodihydrofluorescein fluorescence in human mesangial cells (165).…”
Section: B Ros and The Complications Of Diabetesmentioning
confidence: 99%